Integrating Problem-Based and Flipped Learning in Islamic Religious Education: A Pathway to Achieving Sustainable Development Goals - Nugraha, Tubagus Chaeru; Abdel Rahim, El-Sawy El-Sawy Ahmed; Lukman, Fahmy (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
Islamic religious education at universities has not yet become a foundational aspect of scientific discipline thinking. This study aims to explore the role of Islamic religious education in achieving Sustainable Development Goals (SDGs). A descriptive analysis method was employed, incorporating data collection through selected questionnaires and interviews, content analysis of the gathered data, and presentation of the results in tables with descriptive and explanatory explanations. The findings indicate that Islamic religious education, when implemented through a well-designed Problem-Based Learning (PBL) method, effectively trains students to provide paradigmatic solutions to issues related to population, the planet, and the economy. This approach fosters an academic atmosphere that encourages learning and enthusiasm among students. The PBL design equips students with the skills to apply Islamic concepts and methods as comprehensive solutions to various environmentally friendly challenges concerning population, planet, and economic issues. In conclusion, integrating PBL in Islamic religious education at universities enhances students' ability to address SDGs, promoting sustainable development through the application of Islamic principles.